Heart failure impairs the mechanotransduction properties of human cardiac pericytes. (February 2021) - Rolle, Irene Giulia; Crivellari, Ilaria; Zanello, Andrea; Mazzega, Elisa; Dalla, Emiliano; Bulfoni, Michela; Avolio, Elisa; Battistella, Alice; Lazzarino, Marco; Cellot, Alice; Cervellin, Celeste; Sponga, Sandro; et al.
Abstract: The prominent impact that coronary microcirculation disease (CMD) exerts on heart failure symptoms and prognosis, even in the presence of macrovascular atherosclerosis, has been recently acknowledged. Experimental delivery of pericytes in non-revascularized myocardial infarction improves cardiac function by stimulating angiogenesis and myocardial perfusion. Aim of this work is to verify if pericytes (Pc) residing in ischemic failing human hearts display altered mechano-transduction properties and to assess which alterations of the mechano-sensing machinery are associated with the observed impaired response to mechanical cues. Results: Microvascular rarefaction and defects of YAP/TAZ activation characterize failing human hearts. Although both donor (D-) and explanted ( E -) heart derived cardiac Pc support angiogenesis, D-Pc exert this effect significantly better than E-Pc. The latter are characterized by reduced focal adhesion density, decreased activation of the focal adhesion kinase (FAK)/ Crk-associated substrate (CAS) pathway, low expression of caveolin-1, and defective transduction of extracellular stiffness into cytoskeletal stiffening, together with an impaired response to both fibronectin and lysophosphatidic acid. Importantly, Mitogen-activated protein kinase kinase inhibition restores YAP/TAZ nuclear translocation. Conclusion: Heart failure impairs Pc mechano-transduction properties, but this defect could be reversed pharmacologically. Graphical abstract: Unlabelled Image Highlights: End-stage failing ischemic human hearts show microvascular rarefaction. The proangiogenic function of cardiac pericytes is partially exhausted in heart failure. YAP/TAZ are mechanosensitive, pro-angiogenic co-transcriptional regulators. YAP/TAZ nuclear shuttling is reduced in failing hearts-derived cardiac pericytes. This defect could be reversed by pharmacologically inhibiting the MEK/ERK pathway.